Relationship between stock market and macroeconomic variables using panel data with structural breaks: ASEAN-5 countries - Diana Hassan; Assis Kamu; Ricky Chia Chee Jiun; Ho Chong Mun (Penerbit Universiti Malaysia Sabah, 2025)
This study looks at the ASEAN-5 countries and investigates how structural changes affect the relationship between the stock market index and selected macroeconomic variables (interest rate, exchange rate, and industrial production index) using panel data analysis from January 2012 to December 2022. Applying the panel date regression techniques, the results show that before the structural break period, the random effect model (REM) is appropriate for the estimate model. The stock market index is significantly affected by the interest rate and industrial production index, but the exchange rate is found to be insignificant. After structural break, a fixed effect model (FEM) is appropriate where all significant and only the exchange rate is found to be negative. The findings of this paper also conclude that the industrial production index has a greater effect on both the model before and after a break and is positively related to the stock market index. In this case, there is a need for amendments in monetary policy to ensure that the industrial production index is set at a high level, since the results would be able to boost the stock market in the selected ASEAN-5 countries.